Histological features of intracranial thrombi in stroke patients with cancer. Issue 1 (7th May 2019) - Park, Hyungjong; Kim, Jayoung; Ha, Jimin; Hwang, In Gun; Song, Tae‐Jin; Yoo, Joonsang; Ahn, Seong Hwan; Kim, Kyoungsub; Kim, Byung Moon; Kim, Dong Joon; Kim, Young Dae; Nam, Hyo Suk; et al.
Abstract : The histological features of thrombus in stroke patients with cancer are not well known. Using immunohistochemical staining of thrombi retrieved during mechanical thrombectomy in stroke patients, thrombus compositions were compared between 16 patients with active cancer, 16 patients with inactive cancer, and 16 patients without any history of cancer. The active cancer group showed higher platelet and lower erythrocyte fractions than the inactive cancer or the control group. Four patients with vegetation showed very high platelet and low erythrocyte fractions. Patients with cryptogenic etiology in the active cancer group showed a similar pattern to those with vegetation. These findings may aid the determination of treatment strategies in cancer‐associated stroke. ANN NEUROL 2019